Associations of adverse childhood experiences with caries and toothbrushing in adolescents. The Young-HUNT4 Survey - Lena Myran; Abhijit Sen; Tiril Willumsen; Audun Havnen; Therese Kvist; Anne Rønneberg; Göran Dahllöf; Hedda Høvik (BMC, 2023)
Abstract Background Adverse childhood experiences (ACEs) are associated with poor oral health. Using a life course theoretical framework, this study explored the associations of specific and cumulative ACEs with caries and toothbrushing frequency in a Norwegian adolescent population. Methods Participants were adolescents (n = 6351) age 13-17 years from The Young-HUNT4 Survey. Clinical data were retrieved from dental health records. Oral health outcomes were toothbrushing frequency, dentine caries experience (Decayed, Missing, and Filled Teeth - DMFT), and enamel caries. ACE exposure variables were physical abuse, sexual abuse, witness to violence, parental separation/divorce, parental alcohol problems, and bully victimization. Negative binominal regression models (incident rate ratios, IRRs; 95% confidence intervals, CIs) were used to determine the associations of the various ACEs with caries; logistic regression analyses (odds ratios, ORs; 95% CIs) were used to estimate associations with toothbrushing frequency. Potential effect modification by age was assessed using likelihood ratio test. Results Adolescents exposed to physical abuse by others, sexual abuse by peers, parental separation/divorce, bullying, or who had witnessed violence, were more likely to report non-daily toothbrushing compared with those with no exposure to the given ACEs. Each cumulative increase in ACE exposure was associated with a 30% higher likelihood of non-daily toothbrushing (OR 1.30, 95% CI 1.19-1.42). Similarly, increasing number of adversities were associated with both higher dentine caries experience (IRR 1.06, 95% CI 1.02-1.09) and higher enamel caries (IRR 1.07, 95% CI 1.03-1.11). This effect was modified by age (13-15 vs. 16-17 years) for dentine caries experience. Furthermore, there was evidence of effect modification by age with bully victimization for both toothbrushing frequency (Pinteraction = 0.014) and dentine caries experience (Pinteraction < 0.001). Specifically, bully victimization was associated with a higher likelihood of non-daily toothbrushing (OR 2.59, 95% CI 1.80-3.72) and higher dentine caries experience (IRR 1.30, 95% CI 1.14-1.50) among 16-17-year-olds. Conclusions Several specific ACEs were associated with non-daily toothbrushing and a higher caries experience among Norwegian adolescents in the Young-HUNT4 Survey.